Observation Results of the Effect of Pre breaker Machines on Raw Rubber Products at PT Bridgestone Sumatra Rubber Estate - Aritonang, Surya Darma; Purba, Jhon Sufriadi (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This report presents the results of a field observation on the strategic role of the prebreaker machine in improving the quality of crumb rubber of the Standard Indonesian Rubber 20 (SIR 20) type at PT Bridgestone Sumatra Rubber Estate. The background of this observation is based on the complexity of processing raw rubber materials (Bokar), which are often contaminated by organic and inorganic materials that can reduce the physical integrity of tire products. The main objective of the observation is to evaluate the mechanical effectiveness of the prebreaker machine in reducing material size, improving contaminant removal efficiency, and preparing the rubber structure for optimal drying stages. The methods applied include participatory observation on the wet processing line, technical sampling, and comparative analysis of quality control laboratory data during the fieldwork practice period. The results indicate that the use of the prebreaker machine significantly reduces dirt content to below the threshold of 0.16% in accordance with SNI 1903:2011 standards and minimizes the formation of white spot defects through improved crumb homogeneity. The conclusion of this study confirms that optimizing blade configuration and rotational speed of the prebreaker machine is a key determinant in producing raw rubber that meets the technical specifications of the global automotive industry, while also supporting energy efficiency in subsequent production stages.